2002
DOI: 10.1021/bi0263513
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Mechanism of Cdc25

Abstract: Cdc25 is a dual-specificity phosphatase that catalyzes the activation of the cyclin-dependent kinases, thus causing initiation and progression of successive phases of the cell cycle. Although it is not significantly homologous in sequence or structure to other dual-specificity phosphatases, Cdc25 belongs to the class of well-studied cysteine phosphatases as it contains their active site signature motif. Like other dual-specificity phosphatases, Cdc25 contains an active site cysteine whose pK(a) of 5.9 can be m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 42 publications
4
49
0
1
Order By: Relevance
“…The tissue-specific activity of the PAcP promoter has already been reported (Zelivianski et al 1998, 2002, Shan et al 2003. For example, deletion analyses of the PAcP promoter revealed that p779 (0 to x779 bp fragment) S Veeramani et al: cPAcP in androgen-independent prostate cancer progression has the basal promoter activity and p1356 (0 to x1356 bp fragment) exhibits the prostate specificity (Zelivianski et al 2004).…”
Section: Cpacp: a Tumor Suppressor Phosphatasementioning
confidence: 97%
See 1 more Smart Citation
“…The tissue-specific activity of the PAcP promoter has already been reported (Zelivianski et al 1998, 2002, Shan et al 2003. For example, deletion analyses of the PAcP promoter revealed that p779 (0 to x779 bp fragment) S Veeramani et al: cPAcP in androgen-independent prostate cancer progression has the basal promoter activity and p1356 (0 to x1356 bp fragment) exhibits the prostate specificity (Zelivianski et al 2004).…”
Section: Cpacp: a Tumor Suppressor Phosphatasementioning
confidence: 97%
“…Sequence homology analyses of PAcP revealed that it contains neither the PTP signature motif, C(X) 5 R(S/T), nor the extended active site signature sequence for the dual-specificity phosphatases, VXV HCXXGXXRS(X) 5 AY(L/I)M (Vihko et al 1988, Roiko et al 1990, Jackson & Denu 2001, Rudolph 2002 , which bears a free sulfhydryl group, is located in the interior pocket of the active site of PAcP . Chemical titration experiments confirmed that PAcP has two reactive sulfhydryl groups (Ostanin et al 1994).…”
Section: Structural Analysis Of Cpacpmentioning
confidence: 99%
“…The contrasting results in these two systems must therefore originate from other differences. First, the rate of association for Barnase/Barstar is truly diffusion-limited (k on = 10 9 M −1 s −1 (Schreiber and Fersht 1996), ΔH ‡ = 4 kcal/mol (Frisch and others 2001), strong viscosity dependence (Schreiber and Fersht 1996)), in contrast to Cdc25B/Cdk2-pTpY/CycA (k on = 10 6 M −1 s −1 , ΔH ‡ = 13 kcal/mol, no viscosity dependence (Rudolph 2002)). Second, the effects of individual mutations for the Barnase/Barstar system on the rate of association are small compared to what we have observed for our hotspot mutants (~10-fold vs. ≥ 200-fold), with most mutations in Barnase/Barstar affecting the rates of dissociation.…”
Section: The Temperature Dependence Of Es Formation For Cdc25b With mentioning
confidence: 99%
“…For wild type Cdc25B, the overall Gibbs free energy barrier is 17 kcal/mol at 298 K with a ΔH ‡ of 12 kcal/mol and a TΔS ‡ of -6 kcal/ mol. The smaller ΔH ‡ in formation of the phospho-cysteine for protein substrate compared to pNPP may reflect the favorable contribution by the yet unidentified catalytic acid in protonation of the leaving group (Chen and others 2000;Rudolph 2002;Rudolph 2005). Alternatively, the hydrophobic environment afforded by the protein interface (Sohn and others 2005), which favors stabilization of a meta-phosphate-like transition state, may be responsible for this difference in ΔH ‡ values.…”
Section: The Temperature Dependence Of Phosphate Transfer For Cdc25b mentioning
confidence: 99%
“…Por exemplo, este modelo pode explicar porque enzimas CDC25 da família das PTPs desfosforilam o substrato natural (a proteína CDK2) 10 3 vezes mais rápido que substratos artificiais que possuem apenas uma região reativa e nenhuma região de ligação 32 .…”
Section: Modelo Do Sítio Divididounclassified